Fear of Movement Is Not Associated With Objective and Subjective Physical Activity Levels in Chronic Nonspecific Low Back Pain - Carvalho, Flavia A. [UNESP] (2017)
Objectives: To assess the association of physical activity measures, derived with an accelerometer and a self-reported questionnaire, with fear of movement in patients with chronic nonspecific low back pain (LBP) and to investigate the association between disability and fear of movement in this population. Design: Cross-sectional study. Setting: Outpatient physical therapy university clinics. Participants: Patients (N=119) presenting with nonspecific LBP of >3 months' duration. Interventions: Not applicable. Main Outcome Measures: Physical activity levels measured objectively with an accelerometer (ie, counts per minute, time spent in moderate to -vigorous and light physical activity per day, number of steps per day, and number of 10-minute bouts of moderate-to-vigorous physical activity per day) and subjectively with a self-reported questionnaire (Baecke Physical Activity Questionnaire); fear of movement (Tampa Scale of Kinesiophobia); pain (11-point numerical rating scale); disability (Roland Morris Disability Questionnaire); and depression (Beck Depression Inventory). The associations were examined with correlational, univariate, and multivariable linear regression analyses. Results: None of the objective physical activity measures were associated with fear of movement. The apparent association of self-reported physical activity levels with fear of movement (correlational analyses: r=-.18; P<.05; univariate regression analyses: (beta=-.04; 95% confidence interval [CI], -.07 to -.01; P=.04) was not confirmed in multivariable analyses. Fear of movement was consistently associated with disability in both correlational (r=.42; P<.01) and multivariable (beta=.21; 95% CI, .11-31; P<.001) analyses. Conclusions: Our data support one aspect of the fear-avoidance model-that higher fear of movement is associated with more disability-but not the aspect of the model linking fear of movement with inactivity. (C) 2016 by the American Congress of Rehabilitation Medicine